2006
DOI: 10.1099/jmm.0.46204-0
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and phylogenetic analysis of the gene for surface layer protein, slpA, from 14 PCR ribotypes of Clostridium difficile

Abstract: Clostridium difficile is the commonest cause of antibiotic-associated diarrhoea, with the hospitalized elderly being at particular risk. The organism makes a crystalline surface protein layer (S-layer), encoded by the slpA gene, the product of which is cleaved to give two mature peptides which associate to form the layer. The larger peptide (high molecular weight; HMW), derived from the C-terminal portion of the precursor, is relatively conserved, whereas the smaller peptide (low molecular weight; LMW), derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 47 publications
3
42
0
Order By: Relevance
“…The cleavage at the N-terminal domain is heterogeneous, with the major cleavage site identi- fied at Lys-91, in accordance with the recent results from de la Riva et al (11). It is noteworthy that the consensus cleavage site of SlpA into the mature S-layer proteins is also located after a serine residue (13,14), but no other consensus motif has been recovered in Cwp84. The C-terminal cleavage site has been presumably identified at Lys-518.…”
Section: Discussionsupporting
confidence: 78%
“…The cleavage at the N-terminal domain is heterogeneous, with the major cleavage site identi- fied at Lys-91, in accordance with the recent results from de la Riva et al (11). It is noteworthy that the consensus cleavage site of SlpA into the mature S-layer proteins is also located after a serine residue (13,14), but no other consensus motif has been recovered in Cwp84. The C-terminal cleavage site has been presumably identified at Lys-518.…”
Section: Discussionsupporting
confidence: 78%
“…Both SLPs are encoded by a single gene, slpA, and are produced from the post-translational cleavage of a common precursor: the HMW SLP is derived from the Cterminal portion of the precursor, whereas the LMW SLP is derived from the N-terminal portion (Calabi et al, 2001). Sequence variability is particularly evident in the LMW SLP but is also present in the HMW SLP, giving rise to a range of protein sizes Eidhin et al, 2006). Studies on S-layer adhesive properties have demonstrated that chemical removal of the SLPs or treatment with anti-SLP antibodies can abolish adherence of C. difficile to human HeLa or mouse 929 cells .…”
Section: Introductionmentioning
confidence: 99%
“…43 We and others have shown that SlpA is a major contributor to C. difficile adherence, and that inhibition of adherence can be exploited as a strategy to prevent C. difficile binding to biotic surfaces. 44 SLPs have also been implicated in immune modulation associated with CDI; 45 thus, these proteins are critical non-toxin virulence factors.…”
Section: Other C Difficile Virulence Factorsmentioning
confidence: 99%